1999
DOI: 10.1093/jn/129.4.890
|View full text |Cite
|
Sign up to set email alerts
|

Net Postprandial Utilization of [15N]-Labeled Milk Protein Nitrogen Is Influenced by Diet Composition in Humans

Abstract: The aim of this study was to follow the fate of dietary nitrogen to assess the postprandial utilization of purified milk protein and to determine the acute influence of energy nutrients. For this purpose, a [15N]-labeling dietary protein approach was used. Twenty-five subjects swallowed an ileal tube and ingested [15 N]-milk protein alone or supplemented with either milk fat or sucrose. The absorption and postprandial deamination of dietary protein was monitored for 8 h. Sucrose delayed the absorption of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 28 publications
8
72
0
Order By: Relevance
“…Carbohydrates are known to reduce amino acid catabolism during the postprandial phase, both directly and through their insulin-releasing effect. In a previous study with 15 N-labeled milk protein, we showed that glucose diverts some dietary nitrogen from postprandial deamination (9). There are many reasons dietary and endogenous amino acids, which follow different routes and metabolic kinetics, may not be similarly affected by the addition of carbohydrates.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Carbohydrates are known to reduce amino acid catabolism during the postprandial phase, both directly and through their insulin-releasing effect. In a previous study with 15 N-labeled milk protein, we showed that glucose diverts some dietary nitrogen from postprandial deamination (9). There are many reasons dietary and endogenous amino acids, which follow different routes and metabolic kinetics, may not be similarly affected by the addition of carbohydrates.…”
Section: Introductionmentioning
confidence: 89%
“…Breath samples were collected every 30 min and stored until later determination of 13 CO 2 isotopic enrichment. Urine was collected over a 29-h period (0-2, 2-4, 4-6, 6-8, [8][9][10][11][12][12][13][14][15][16][17][18][19][20], and 20-29 h after meal ingestion), treated with thymol crystals and liquid paraffin as preservatives, and stored at 4 ЊC until analyzed.…”
Section: Clinical Protocolmentioning
confidence: 99%
“…Although the digestion of alimentary protein is very efficient, approximately 90% efficiency, some nitrogenous material originating from non-digested proteins are transferred from the small intestine to the large intestine [7] and are degraded by the microbiota and by residual pancreatic enzymes to produce numeral metabolites and gases. These gases, especially, can be beneficial or deleterious for the intestinal epithelium in a concentrationdependent way [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are generally conducted at steady state for practical reasons (i.e., during the fasting period when no proteins are administered or in an artificial fed state, where steady-state is achieved through the constant intragastric administration of a meal). Only a few studies have been conducted under physiological conditions in the fed state (i.e., the meal being ingested as a bolus) and have thus provided a valuable insight into the dynamic and adaptative features of protein metabolism [6,20,21].…”
Section: Introductionmentioning
confidence: 99%